2016
DOI: 10.1021/acs.jchemed.6b00062
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing Instructional Practices in the Laboratory: The Laboratory Observation Protocol for Undergraduate STEM

Abstract: Chemistry laboratories play an essential role in the education of undergraduate Science, Technology, Engineering, and Mathematics (STEM) and non-STEM students. The extent of student learning in any educational environment depends largely on the effectiveness of the instructors. In chemistry laboratories at large universities, the instructors of record are typically graduate or undergraduate teaching assistants (TAs). Despite the importance of their role in the education of undergraduate students, TAs' instruct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
90
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(99 citation statements)
references
References 67 publications
4
90
0
1
Order By: Relevance
“…As such, they still must complete coursework, conduct novel research, and in many cases teach at the undergraduate level. Many graduate students in STEM disciplines teach; for example, in biology, 70-90% of laboratory courses in large research universities are taught by TAs (21,22) and TAs primarily teach introductory level lab courses (23). Previous work suggests that graduate students, particularly TAs, can feel out of place – that they are neither “fish nor fowl” – while navigating their roles as student, teacher, and researcher (24).…”
Section: Introductionmentioning
confidence: 99%
“…As such, they still must complete coursework, conduct novel research, and in many cases teach at the undergraduate level. Many graduate students in STEM disciplines teach; for example, in biology, 70-90% of laboratory courses in large research universities are taught by TAs (21,22) and TAs primarily teach introductory level lab courses (23). Previous work suggests that graduate students, particularly TAs, can feel out of place – that they are neither “fish nor fowl” – while navigating their roles as student, teacher, and researcher (24).…”
Section: Introductionmentioning
confidence: 99%
“…Initially, data obtained from the observation instruments were only analysed to capture behaviours (Kyle et al, 1979;Lehman, 1990), while in the later years, results from the instruments were connected with other data to understand the impacts of interactions (Hilosky et al, 1998), or with the investigation of student engagement (Sadler et al, 2011;Stang & Roll, 2014). The studies were also improved by the integration of more theories as guidance (Velasco et al, 2016).…”
Section: Discussion and Future Directionsmentioning
confidence: 99%
“…The Internet also improved efficiency in communication and information exchange between different institutions. Based on the theory developed by Cohen and Ball (1999) that interactions between students, instructor, and materials each influence instructional capacities, Velasco et al (2016) developed an observation instrument -the Laboratory Observation Protocol for the Undergraduate STEM (LOPUS) -to investigate the TAs' instructional practices. It was found that students' behaviours were independent of TAs' instructional characteristics, and the TA initiated fewer verbal conversations than did the students.…”
Section: Variations Of Measurement Tools In Face-to-face Science Labomentioning
confidence: 99%
“…Observation protocols can provide data that illustrate what happened in the class, which can be useful for self-reflection and professional development. You can use observation protocols once as stand-alone activity, or to track your own improvement.Observational protocols can be conducted using segmented, continuous, and holistic procedures 61. Segmented protocols are those in which the class period is broken up into shorter periods of time, two-minute intervals for example, and then observers notewhether they see certain behaviors during that interval or not.…”
mentioning
confidence: 99%